![image](https://tex.z-dn.net/?f=%28%5Csqrt%7B2%2B%5Csqrt%7B3%7D%7D%29%5Ex%2B%28%5Csqrt%7B2-%5Csqrt%7B3%7D%7D%29%5Ex%3D4+%7C%2A%28%5Csqrt%7B2-%5Csqrt%7B3%7D%7D%29%5Ex%5C%5C1+%2B+%28%5Csqrt%7B2-%5Csqrt%7B3%7D%7D%29%5E%7B2x%7D+%3D4%28%5Csqrt%7B2-%5Csqrt%7B3%7D%7D%29%5Ex%5C%5C%28%5Csqrt%7B2-%5Csqrt%7B3%7D%7D%29%5Ex%3Dt+%28t%3E0%29%5C%5Ct%5E2-4t%2B1%3D0%5C%5CD%2F4%3D4-1%3D3%5C%5Ct_1%3D2%2B%5Csqrt%7B3%7D+%5C%5C+t_2+%3D+2-%5Csqrt%7B3%7D%5C%5C+%5C%5C+%28%5Csqrt%7B2-%5Csqrt%7B3%7D%7D%29%5Ex%3Dt+%5C%5C+%5C%5C+1%29+%28%5Csqrt%7B2-%5Csqrt%7B3%7D%7D%29%5Ex+%3D+2%2B%5Csqrt%7B3%7D+%7C%2A+%28%5Csqrt%7B2%2B%5Csqrt%7B3%7D%7D%29%5Ex%5C%5C+1+%3D+%28%5Csqrt%7B2%2B%5Csqrt%7B3%7D%7D%29%5E%7Bx%2B2%7D%5C%5Cx%2B2%3D0%5C%5Cx%3D-2%5C%5C%5C%5C2%29+%28%5Csqrt%7B2-%5Csqrt%7B3%7D%7D%29%5Ex%3D++2-%5Csqrt%7B3%7D%5C%5Cx%3D2+)
0)\\t^2-4t+1=0\\D/4=4-1=3\\t_1=2+\sqrt{3} \\ t_2 = 2-\sqrt{3}\\ \\ (\sqrt{2-\sqrt{3}})^x=t \\ \\ 1) (\sqrt{2-\sqrt{3}})^x = 2+\sqrt{3} |* (\sqrt{2+\sqrt{3}})^x\\ 1 = (\sqrt{2+\sqrt{3}})^{x+2}\\x+2=0\\x=-2\\\\2) (\sqrt{2-\sqrt{3}})^x= 2-\sqrt{3}\\x=2 " alt="(\sqrt{2+\sqrt{3}})^x+(\sqrt{2-\sqrt{3}})^x=4 |*(\sqrt{2-\sqrt{3}})^x\\1 + (\sqrt{2-\sqrt{3}})^{2x} =4(\sqrt{2-\sqrt{3}})^x\\(\sqrt{2-\sqrt{3}})^x=t (t>0)\\t^2-4t+1=0\\D/4=4-1=3\\t_1=2+\sqrt{3} \\ t_2 = 2-\sqrt{3}\\ \\ (\sqrt{2-\sqrt{3}})^x=t \\ \\ 1) (\sqrt{2-\sqrt{3}})^x = 2+\sqrt{3} |* (\sqrt{2+\sqrt{3}})^x\\ 1 = (\sqrt{2+\sqrt{3}})^{x+2}\\x+2=0\\x=-2\\\\2) (\sqrt{2-\sqrt{3}})^x= 2-\sqrt{3}\\x=2 " align="absmiddle" class="latex-formula">
Ответ: ±2